UNIT 9.42 Multiparameter Analysis of Apoptosis Using Lab‐on‐a‐Chip Flow Cytometry. Issue 1 (9th October 2013) - Wlodkowic, Donald; Skommer, Joanna; Akagi, Jin; Fujimura, Yoo; Takeda, Kazuo
Abstract: The age of microfluidic flow cytometry (µFCM) is fast becoming a reality. One of the most exciting applications of miniaturized chip‐based cytometers is multivariate analysis using sampling volumes as small as 10 µl while matching the multiparameter data collection of conventional flow cytometers. We outline several innovative protocols for analyzing caspase‐dependent cell death and cell cycle (DNA‐content) profile using a fully integrated microfluidic flow cytometry system, Fishman‐R. The first protocol describes the use of a new plasma membrane–permeability marker, DRAQ7, and the fluorogenic caspase substrate PhiPhiLux to track caspase activation during programmed cell death. Also outlined is the use of DRAQ7 fluorochrome in conjunction with the mitochondrial membrane potential–sensitive probe TMRM to track dissipation of inner mitochondrial cross‐membrane potential. Another protocol adds the ability to measure dissipation of mitochondrial inner membrane potential (using TMRM probe) in relation to the cell cycle profile (using DRAQ5 probe) in living leukemic cells. Finally, we describe the combined use of fluorogenic caspases substrate PhiPhiLux with DRAQ5 probe to measure caspase activation in relation to the cell cycle profile in living tumor cells. Curr. Protoc. Cytom . 66:9.42.1‐9.42.15. © 2013 by John Wiley & Sons, Inc.